CONSTRUCT VALIDATION OF ENTREPRENEURIAL CHARACTER SCALE - Husna, Aftina Nurul; Akmal, Nur (Jurnal Psikologi, 2020)
This article reports on the effort to test psychometric properties of the revised version of Skala Karakter Wirausaha (SK-Wira). The research aims to clarify the scale’s internal structure by examining its construct validity. Construct validity is proven through confirming the internal structure and associating the scale with relevant variables. Revised version of SK-Wira and other measures were administered to university students in Magelang and Makassar (N = 598). After completing CFA, Study 1 confirmed that SK-Wira can be used as both multidimensional scale (model 1) to measure general entrepreneurial character, and unidimensional scales (model 2) to measure specific domains separately. Both models showed good fit. In Study 2, general and specific domains of entrepreneurial character were correlated with hope of success, fear of failure, openness to experience, neuroticism, entrepreneurial intention, and entrepreneurial self-efficacy. The results accepted all proposed hypotheses. In conclusion, SK-Wira is a valid instrument to measure entrepreneurial character for psychology of entrepreneurship research.